Effect of Papain Enzyme in Feed on Digestibility of Feed, Growth Performance, and Survival Rate in Post Larvaes of Freshwater Lobster [Cherax quadricarinatus (Von Martens, 1868)]: Effect of Papain Enzyme on Freshwater Lobster - Rachmawati, Diana; Prihanto, Asep Awaludin; Setyobudi, Roy Hendroko; Anne, Olga (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
The study aimed to find the impact of additional papain enzyme in feed digestibility, growth performance, and survival rate in post larvaes of freshwater lobster [Cherax quadricarinatus (Von Martens, 1868)]. There were five treatments with dosage A (0 % papain enzyme per kg feed), B (0.1 % papain enzyme per kg feed), C (0.2 % papain enzyme per kg feed), D (0.3 % papain enzyme per kg feed) and E (0.4 % papain enzyme per kg feed). Every treatment was repeated three times. The experiment used Completely Randomized Design. EFU (Efficiency of Feed Utilization), FCR (Feed Conversion Ratio), PER (Protein Efficiency Ratio), RGR (Relative Growth Rate), ADCP (Apparent Digestibility Coefficient of Protein), SR (Survival Rate) and water quality parameters were determined. The study found that the impacts of the various dosages of papain enzyme exhibited significant effects (P < 0.01) on the EFU, FCR, PER, RGR, ADCP; however, insignificant effects were observed (P > 0.05) on the survival rate of freshwater lobster. It was concluded that the incorporation of papain enzyme improved the feed digestibility and the growth performance of post larvae in freshwater lobster. The study found that optimum dosages of papain enzyme on feed digestibility, efficiency of feed utilization and growth rate of freshwater lobster ranged from 0.24 % to 0.31 % papain enzyme per kg feed. The quality of media culture was still in the feasible condition for post larvae of freshwater lobster cultivation.